Rancangan Aplikasi Kasir Toko Kelontong Berbasis Website Menggunakan Metode Waterfall - Irmayanti, Ade; Ruspita, Desi (IKRA-ITH Informatika : Jurnal Komputer dan Informatika, 2025)
Digitalization in the business world has become an urgent need to enhance efficiency andproductivity, particularly for grocery stores that still rely on manual methods for managingtransactions and inventory. Dependence on manual processes often leads to various issues, such asinaccurate record-keeping, difficulties in tracking inventory, and suboptimal customer service. Toaddress these challenges, this study develops a web-based cashier application designed to automatetransactions, inventory management, and sales reporting. The application is expected to facilitatestore owners in managing daily operations while improving data accuracy and customersatisfaction. The development of the application follows the Waterfall method, a structured andlinear software development approach. This method involves stages of requirements analysis,system design, implementation, testing, and maintenance. The outcome of this study is a webbasedcashier application capable of addressing the challenges faced by grocery stores, withfeatures that support operational efficiency and flexibility in monitoring business activities. Thisapplication also offers long-term benefits in enhancing the competitiveness of grocery stores in thedigital era.